Repeated applications of cold atmospheric pressure plasma does not induce resistance in Staphylococcus aureus embedded in biofilms - Matthes, Rutger; Assadian, Ojan; Kramer, Axel (German Medical Science GMS Publishing House, 2014)
[english] Introduction: The increasing microbial resistance against antibiotics complicates the therapy of bacterial infections. Therefore new therapeutic options, particularly those causing no resistance, are of high interest. Cold atmospheric plasma is one possible option to eradicate multidrug resistant microorganisms, and so far no resistance development against physical plasma is known.Method: We tested 6-fold repeated plasma applications on a strain embedded in biofilm and compared the reduction of the colony forming units between the different treatment periods to asses a possible development of resistance.Result: For all treatment periods, the control biofilms were reduced by plasma in average by 1.7 log CFU, and decreased from 7.6 to 5.8 log (CFU/cm) within 5 hours. The results demonstrated that repeated plasma doses not induce resistance or habituation against plasma applied within short time periods.Conclusion: The repeated application of cold plasma is a promising option for the treatment of infected wounds without the risk of development of resistance against plasma.